Territorial Identities as Social Constructs - Paasi, Anssi (Hagar: Studies in Society and Culture, 2000)
Identity is one of the keywords of contemporary social and cultural science. Space and territory are social and cultural constructs that occupy a crucial position in the construction and maintenance of spatial identities. In spite of this fact their meanings have not been widely discussed in the literature. Identities and boundaries are two sides of the same coin: collective identities are typically constructed in the relations of one social grouping to another. Both identity and boundaries thus reflect power relations that are part of the social practices of inclusion and exclusion. As a concrete illustration of their conceptual analysis, this paper evaluates the interpretations of Finnish national identity. This has from the dawn of Finland’s independence been constructed in relation to images of threat, particularly that of the Soviet Union/Russia. The new geopolitical context in Europe has in many ways challenged the constituents of former images, and a debate on Finnish identity emerged with entry into the European Union in 1995, leading to discussions of issues such as the existence of a specific Finnish national culture and identity, immigration, citizenship, sovereignty and security policy. This is therefore a fitting illustration of the tendencies for re-territorialization that occur in the current globalizing world.